4 3 + 2 1 + 1 6 7 + 3 2 1 1 + 6 4 1 8 + … = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How do you know that the series converges? I am afraid without that given proof your approach is incorrect, but at least incomplete.
We need first to prove that the series converges. For that we use the ratio test. But before that, first observe that the numerators are in a Fibonacci sequence with starting terms 3 and 4. Hence, if a and b are two consecutive numerators then b < a < 2 b . Let us denote the numerator sequence as ( F n ) n ≥ 1 and let R n = F n F n + 1 , ∀ n ∈ N . Then we have F n + 1 = F n + F n − 1 and R n = 1 + R n − 1 1 . We shall show that this ratio sequence goes to the Golden Ratio ϕ given by: ϕ = 1 + ϕ 1 . We see that: ∣ R n − ϕ ∣ = ∣ ∣ ∣ ∣ ( 1 + R n − 1 1 ) − ( 1 + ϕ 1 ) ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ R n − 1 1 − ϕ 1 ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ ϕ R n − 1 ϕ − R n − 1 ∣ ∣ ∣ ∣ ≤ ( ϕ 1 ) ∣ ϕ − R n − 1 ∣ ≤ ( ϕ 1 ) n − 1 ∣ R 1 − ϕ ∣ Which clearly shows that ( R n ) ⟶ ϕ Now we look at the given series and apply the ratio test on it. If we denote the n-th term of the series as x n then we find that x n x n + 1 = 2 F n F n + 1 . Now the RHS obviously has limit 2 ϕ ≈ 2 1 . 6 1 8 ≈ 0 . 8 0 9 < 1 . Hence ratio test is satisfied and the series converges. The rest of the proof is just same as what Tanishq provided.
Problem Loading...
Note Loading...
Set Loading...
Note in the third step
2 3 + ( 4 4 − 4 3 ) + ( 8 7 − 8 4 ) + . . .